1994
DOI: 10.1590/1809-43921994243302
|View full text |Cite
|
Sign up to set email alerts
|

CONSUMO DE ALIMENTO POR UM GAFANHOTO NEOTROPICAL, Stenacris fissicauda fissicauda (BRUNER, 1908) (ORTHOPTERA:ACRIDIDAE) DA VÁRZEA AMAZÔNICA

Abstract: 1RESUMO -É feita a determinação da quantidade média (g) de biomassa foliar consumida por 1 g (peso seco) de gafanhoto/dia nesta espécie. O material para a realização dos experimentos foi coletado na ilha de Marchantaria (várzea -Rio Solimões) perto de Manaus. Os animais testados foram agrupados por estádio ninfal (ninfas iniciais (I+II), médias (111+lV) e finais (V+VI)) e os adultos pelo sexo (machos, fêmeas, machos+fêmeas). A planta utilizada como alimento foi Paspalwn repens, macrófita aquática das Poaceac, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 3 publications
2
4
1
Order By: Relevance
“…The CI of C. aquaticum found in our study is higher than the consumption found for other semiaquatic grasshoppers (Thomas 1974, Amorim & Adis 1994. Based on the amount of consumption reported by Amorim & Adis (1994) for Stenacris fissicauda fissicauda (Leptysminae), we estimated the CI for the different specific age classes of this Amazonian grasshopper (nymphs A: 0.774, nymphs B: 0.473-0.502 and adults: 0.262). Because the mean individual dry weights of both Leptysminae species are similar, thus, we postulate that C. aquaticum has a greater consumption capacity than S. fissicauda fissicauda.…”
Section: Food Consumption Of C Aquaticumcontrasting
confidence: 53%
See 3 more Smart Citations
“…The CI of C. aquaticum found in our study is higher than the consumption found for other semiaquatic grasshoppers (Thomas 1974, Amorim & Adis 1994. Based on the amount of consumption reported by Amorim & Adis (1994) for Stenacris fissicauda fissicauda (Leptysminae), we estimated the CI for the different specific age classes of this Amazonian grasshopper (nymphs A: 0.774, nymphs B: 0.473-0.502 and adults: 0.262). Because the mean individual dry weights of both Leptysminae species are similar, thus, we postulate that C. aquaticum has a greater consumption capacity than S. fissicauda fissicauda.…”
Section: Food Consumption Of C Aquaticumcontrasting
confidence: 53%
“…According to the longevity of each specific age class of the C. aquaticum population (Franceschini 2008), individual cumulative consumption of a specific age class (C cum ) was calculated using the criteria of Amorim & Adis (1994):…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophyte species may also harbor different invertebrate assemblages(Amorim & Adis, 1994;Vieira & Adis, 2000;Adis & Victoria, 2001), which are prey for fish, resulting in an indirect relationship between plant and fish species in the stands along the banks. Stands with different macrophyte compositions have different habitat complexity and macroinvertebrate and periphyton assemblages…”
mentioning
confidence: 99%